Trend analysis of Islamic educational institutions on Indonesian social media in 2018–2023 - Alfina Nur Safitri; Taufik Edy Sutanto; Irma Fauziah (Jurnal Mantik, 2023)
Social media is a valuable means for educational institutions to engage with the wider community. However, it is necessary to understand more deeply how these trends develop in the realm of social media. This study aims to scrutinize the patterns of Islamic education institutions in Indonesia. Islamic Religious Universities (PTKI), Madrasah, and Pesantren were researched through the Google search engine and Google Trends to collect data from social media content and search queries. The social media platforms analyzed were Facebook, Instagram, Twitter, TikTok, and YouTube. An analysis of social media content was conducted to identify trends associated with Islamic education institutions. Additionally, the study employed Google Trends data to compare the available content and gain an empirical depiction of public interest in related subjects. The findings demonstrate that YouTube has a higher availability of content pertaining to “PTKI” (42.6%), while Facebook has a higher availability of content on “pesantren” (57.1%) and “madrasah” (51.6%). The correlation of content data with search data shows a weak correlation, so there is no empirical evidence that increasing content availability affects interest in content search. This research is significant in revealing the extent to which social media content reflects people's interests